Students’ Creativity Profiles in Constructing Independent Gates Learning Activity Using 4Dframe - Agus Setio; Gusnandar Yoga Utama (Southeast Asian Mathematics Education Journal, 2022)
Creativity is one of the 21st century skills that students require for the future. The implementation of STEAM education in teaching and learning, whether in content or learning activities, has contributed to the creativity development. The objective of the study is to investigate the students’ creativity profiles by employing STEAM approach and 4Dframe to construct a miniature independence-day memorial gate. This activity was selected because Indonesian Independence Day, organized in August, is very special. Many activities are frequently conducted to celebrate this annual event. One of which is by building a gate in front of the village. This research utilized a qualitative research method with a narrative design. There was twelve 8th-grade students who were recruited as respondents with various abilities grouped into high, medium, and low. The student’s products were evaluated by CPAM (Creative Product Analysis Matrix) instrument. The CPAM assessment score presented 88% in novelty, 72% in resolution, and 88% in elaboration. Overall, their creativity profile is 82%, included in the high category. The conclusion is that student creativity profile through the STEAM approach assisted by 4Dframe is in the high category and can be applied in learning.